Costos de producción de abonos orgánicos fermentados bocashi de los métodos tecnificado y semitecnificado - Granda Ordoñez, Edison Moises (2005)
Was carried out the study of the costs of production of the payments fermented type (bocashi) of the methods tecnificado and semitecnificado. In the cantons of Machala, Santa Rosa, Pasaje was established the following objectives: 1. to establish the real costs of the payments organic fermented type bocashi of the methods tecnificado and semitecnificado; 2. determination of the relationship weight - production of the techniques in study. For the development of the investigation you visits twice per week each property with the purpose of obtaining the relating data to the production of the payments, inside this obtained information it consists initial weight, final weight, type of used materials, quantity of materials to use, also you sack the relationship weight - production. The production of the payments organic fermented type bocashi was evaluated being determined that the costs go in connection with the materials employees, time of fermentation and temperature. With the purpose of producing organic payments at low cost it is advisable the use of the by-products of the own property.